Grass pea and pea phylogenetic relatedness reflected at Fusarium oxysporum host range. (March 2021) - Sampaio, Ana Margarida; Rubiales, Diego; Vaz Patto, Maria Carlota
Abstract: Vascular wilt, caused by the infection of the soil-borne pathogen Fusarium oxysporum ( Fo ), is one of the most destructive diseases of many crops, including legumes such as grass pea ( Lathyrus sativus ), with several formae speciales (ff. spp.) defined according to their hosts. Commonly described as host-specific, Fo could, in some cases, show a broader host range comprising related plant species, making its host range characterization an important aspect of epidemiology and crop protection. No information on identification and host range status of strains able to infect grass pea is available, nor whether grass pea could act as host to different Fo ff. spp.. In this study, the host range of two Fo strains isolated from grass pea ( Fo ex. L. sativus 1 and 2) was evaluated using related legume species: pea ( Pisum sativum ), lentil ( Lens culinaris ), chickpea ( Cicer arietinum ), common bean ( Phaseolus vulgaris ), and barrel medic ( Medicago truncatula ). In addition, the responses of grass pea to the causal agents of fusarium wilt in these legume species, Fo f. sp. pisi, lentis, ciceris, phaseoli, and medicaginis, were also investigated. Disease symptom evaluation by disease rating over time, its related area under disease progress curve (AUDPC) and disease progress rate (DIr), revealed that Fo ex. L. sativus 1 and 2 are host-specific, infecting only grass pea although with low aggressiveness. Grass pea could also be infected by Fo f. sp. pisi races, with race 2 being the most virulent strain in grass pea, even more virulent than the Fo strains retrieved originally from grass pea. The phylogenetic relatedness between grass pea and pea may in part explain this observation, indicating that Fo f. sp. pisi can also infect legume-related species such as grass pea. Additionally, specialization might be occurring, with particular Fo isolates being only virulent to grass pea, although with lower virulence than Fo f. sp. pisi race 2 itself. These cross-inoculation results reinforce the importance of performing host-range studies, even on specialist pathogens, to identify potential closely related alternative hosts and consequently improve or adapt disease control management. Highlights: Fusarium oxysporum ( Fo ) host range definition is important for disease management. Grass pea is infected by the host-specific Fusarium oxysporum ex. L. sativus . Pea pathogen Fo f. sp. pisi race 2 was the most virulent Fo strain in grass pea. Legume species with phylogenetic proximity can share Fo strains.